American journal of physical anthropology : official publication of the American Association of Physical Anthropologists - American Association of Physical Anthropologists; Johnston, Francis E. (New York : Alan R. Liss, Inc., 1982)
"The American Journal of Physical Anthropology is designed for the prompt publication of original and significant articles on human evolution and variation, including primate morphology, physiology, genetics, adaptation, growth, development, and behavior present and past."
Cortical bone loss and measurements of the second metacarpal bone. I. comparisons between adult Guamanian Chamorros and American Caucasians Plato, C. C., Garruto, R. M., Yanagihara, R. T., Chen, K. M., Wood, J. L., Gajdusek, D. C., and Norris, A. H.
Includes bibliographical references and index.
In English.
Keywords: Physical anthropology -- Periodicals. Societies. Serials; Antiquities, Prehistoric; Prehistoric peoples